PENGARUH KEPRIBADIAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI HOTEL NEO+ KUTA LEGIAN - Komang Ayu Silvi Kumalasari; I Ketut Sutapa; Dewiwati Sujadi (Universitas Triatma Mulya, 2026)
This study aims to determine the effect of Personality and Work Stress on employee performance. The location of this study was at the NEO + Kuta Legian Hotel. Data collection techniques used were observation, questionnaires and documentation. The population used the number of employees at the NEO + Kuta Legian Hotel, with a sample of 60 respondents. The data analysis techniques used were Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Multiple Linear Regression, t-test, f-test, Determination. Based on the results of the study, it was found that Personality has a positive and significant effect on employee performance, Work Stress has a positive and significant effect on employee performance, Personality and Work Stress have an effect of 7.32% on employee performance and work stress variables have a more dominant effect on employee performance. The suggestion that can be given by the researcher is to maintain and improve employee performance and work stress in competition, so that it can improve employee performance. And also provide the best service according to what tourists expect, and always provide innovation in the facilities provided.